The hostile hospital - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2001)
On the run after being falsely accused of murder, the three Baudelaire orphans find themselves in the Heimlich Hospital, with the evil Count Olaf in close pursuit.